2018
DOI: 10.1089/scd.2017.0282
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules for Neural Stem Cell Induction

Abstract: Generation of induced pluripotent stem cells (iPSCs) from other somatic cells has provided great hopes for transplantation therapies. However, these cells still cannot be used for clinical application due to the low reprogramming and differentiation efficiency beside the risk of mutagenesis and tumor formation. Compared to iPSCs, induced neural stem cells (iNSCs) are easier to terminally differentiate into neural cells and safe; thus, iNSCs hold more opportunities than iPSCs to treat neural diseases. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…Then, we found that adding seven small molecules together would cause cell death, which was considered to be due to the possibility of simultaneous inhibition of some signaling pathways or excessive DMSO intake. To overcome this problem, we reviewed related researches and concluded that MET should be promoted in the early induction stage (Zhang et al, 2015; Zheng et al, 2016; Liu et al, 2018). TGF-β signaling plays an important role on modulation of EMT, a process by which an epithelial cell becomes a mesenchymal cell (Grunert et al, 2003), in normal human and mouse (Valcourt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we found that adding seven small molecules together would cause cell death, which was considered to be due to the possibility of simultaneous inhibition of some signaling pathways or excessive DMSO intake. To overcome this problem, we reviewed related researches and concluded that MET should be promoted in the early induction stage (Zhang et al, 2015; Zheng et al, 2016; Liu et al, 2018). TGF-β signaling plays an important role on modulation of EMT, a process by which an epithelial cell becomes a mesenchymal cell (Grunert et al, 2003), in normal human and mouse (Valcourt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β signaling plays an important role on modulation of EMT, a process by which an epithelial cell becomes a mesenchymal cell (Grunert et al, 2003), in normal human and mouse (Valcourt et al, 2005). The generation of iNSCs from MEFs requires an increase in the MET process, through inhibition of TGF-β (Valcourt et al, 2005; Liu et al, 2018). The combination of the TGF-β inhibitor SB431542 and LDN193189 enhances the reprogramming efficiency of MET transition.…”
Section: Discussionmentioning
confidence: 99%
“…24 Conversely, the patterning cues for motor neurons involve neural induction to neuroepithelia with SMADi (LDN193189, SB413542) and a GSK3b inhibitor (CHIR99021) for a week before the addition of retinoic acid and purmorphamine to induce a motor neuron phenotype. 25 Liu et al 26 provide a comprehensive review of commonly used agents in NPC induction (e.g., SMADi LDN193189 and SB431542, transforming growth factor-b family inhibitors, GSK-3 b inhibitors, MAPK signaling pathway inhibitors, and Sonic hedgehog pathway agonists) and also provide insights on epigenetic modifiers that help accelerate iPSC reprogramming (i.e., valproic acid, ascorbic acid, and retinoic acid).…”
Section: Modeling Neurological Diseases With Ipscsmentioning
confidence: 99%
“…Their effects have been specific and reversible [86]. Notable advantage of chemical formulations is that they are easy to handle and cost effective compared to transcription factor-mediated protocols [88]. Moreover, small molecules can aid the progression to feeder-free and serum-free protocols of stem cell culture [89].…”
Section: Small Molecules In Regenerative Medicinementioning
confidence: 99%